AN INDIVIDUAL'S GENDER EXPERIENCE: SOCIO-CULTURAL CONTEXT - Larysa Zahrai (Vasyl Stefanyk Precarpathian National University, 2015)
The article highlights gender experience development in an individual. The socio-cultural context of gender identity development is addressed from the perspective of social constructivism. The author describes the mechanism of constructing gender schemas and norms which reflect socio-cultural experience. Drawing on poststructuralist ideas, the author explores cultural texts which encode assumptions and concepts that serve as schemas for perceiving and understanding reality, for reflecting the processes of an individual's development as a discursive being in his or her interpretation of socio-cultural experience. The article also analyzes masculinity and femininity models shaped by socio-cultural schemas and explores gender role expectations among the young people in Ukraine.